FLC-like factors in wheat (cv. Mv15) and Conyza sp. - Rudnóy, Szabolcs (Acta Biologica Szegediensis, 2002)
Plants have evolved multiple pathwaysto regulate flowering time. The repressor pathway maintains the vegetative phase until the promotion pathways initiate reproductive development. The promotion pathways include the long-day, autonomous and vernalization pathways of flowering. A MADS-box protein encoded by FLOWERING LOCUS C (FLC) may be a major repressor of flowering in vernalization pathway since the transcript level of FLC is negatively regulated by vernalization. Special primer pairs were constructed here to identify the FLC genes in a monocotiledonous plant with strong requirement for vernalization and in a weed. This study describes the first example for the presence of FLC-like factors in winter wheat Triticum aestivum L. cv. MV15 and in the horseweed Conyza canadensis L. (Cronq.).